Microbiota and hepatitis C virus in the era of direct-acting antiviral agents. (February 2023) - Pinchera, Biagio; Moriello, Nicola Schiano; Buonomo, Antonio Riccardo; Zappulo, Emanuela; Viceconte, Giulio; Villari, Riccardo; Gentile, Ivan
Abstract: The gut microbiota plays a fundamental role in Hepatitis C Virus (HCV)-related liver disease. Indeed, HCV infection alters the gut microbiota, whereas intestinal dysbiosis induces an underlying inflammatory state. This status may lead to liver disease progression. The advent of direct acting antivirals (DAAs) was a turning point in the history of HCV infection, which enhances the chances of recovery. Beyond the elimination of the virus, DAA therapy can affect the gut microbiota of the HCV patient. The study of the gut microbiota in the patient with HCV-related liver disease could be the first step in understanding the etiopathogenesis of hepatopathy thereby opening the way to new therapeutic opportunities. Herein we evaluate current knowledge regarding the gut microbiota in patients with HCV infection and the impact of DAA therapy. Highlights: The gut microbiota plays a fundamental role in Hepatitis C Virus (HCV)-related liver disease. HCV infection alters the gut microbiota, whereas intestinal dysbiosis induces an underlying inflammatory state. DAA therapy could affect the gut microbiota of the HCV patient.